COMPUTER AIDED DRUG DESIGNING AND DEVELOPMENT OF NEW NONSTEROIDAL ANTI-INFLAMMATORY DRUGS CONSIDERING MEFENAMIC ACID/ DICLOFENAC AS A LEAD COMPOUND FOLLOWED BY THEIR SYNTHESIS AND EVALUATION - S. B. SURYAAWANSHI; HASSAN.A.OSMAN; G.M. NAZERUDDIN (International Journal of Pharma and Bio Sciences, 2013)
Discovery of new and new non-steroidal anti-inflammatory drug (NSAID) always has attracted greater attention over the years. In the present work series of derivatives of Mefenamic acid and Diclofenac (known non-steroidal anti-inflammatory drugs) were designed and different physicochemical properties were calculated such as Log P, H-Donor, H-Acceptor, Molecular weight and P ka .and these properties are compared with Diclofenac/ Mefenamic Acid. All the new non-steroidal anti-inflammatory drugs (NSAID) selected for designing have to follow Lipinski's Rule of Five. Out of them seven compounds having similar physicochemical properties were selected for the synthesis. They were found to have potential anti-inflammatory activity.